Ultra-processed food consumption, cancer risk and cancer mortality - Chang, Kiara (2023)
Funding Information: The Cancer Research UK and World Cancer Research Fund.This work was supported by Cancer Research UK C33493/A29678. Funding IIG_FULL_2020_033 was obtained from World Cancer Research Fund (WCRF UK), as part of the World Cancer Research Fund International grant programme. Where authors are identified as personnel of the International Agency for Research on Cancer / World Health Organization, the authors alone are responsible for the views expressed in this article and they do not necessarily represent the decisions, policy or views of the International Agency for Research on Cancer / World Health Organization. FR declares funding from The São Paulo Research Foundation (FAPESP) 16/14302-7 and 18/19820-1. This research has been conducted using the UK Biobank Resource under Application Number 29239. The authors would like to thank the participants of the UK Biobank study. Funding Information: This work was supported by Cancer Research UK C33493 / A29678 . Funding IIG_FULL_2020_033 was obtained from World Cancer Research Fund (WCRF UK), as part of the World Cancer Research Fund International grant programme. Where authors are identified as personnel of the International Agency for Research on Cancer / World Health Organization, the authors alone are responsible for the views expressed in this article and they do not necessarily represent the decisions, policy or views of the International Agency for Research on Cancer / World Health Organization. FR declares funding from The São Paulo Research Foundation (FAPESP) 16/14302-7 and 18/19820-1 . This research has been conducted using the UK Biobank Resource under Application Number 29239. The authors would like to thank the participants of the UK Biobank study. Publisher Copyright: © 2023 The Author(s)